BETON BERTULANGAN BAMBU WALESAN - Purnomo, Mego (Semarang State University, 2010)
Bamboo has a tensile strength close to normal steel, it can be used as a substitute tensile steel reinforcement. Bamboo is used with a length of 3 m, base diameter 20 mm, 10 mm tip. Bamboo reinforcement beams in this study is 15 cm x 20 cm x 250 cm. This study uses the characteristic strength of concrete is fc 22 MPa. The tensile strength of bamboo walesan 147.15 Mpa, E 4900 MPa and 3 Listed below dial gauge specimens was investigated. Loading for flexural testing used two concentrated loads. From the results of this research is that keruntuh flexure marked by vertical cracks in the tensile reinforcement. The collapse of the beam is marked with some bamboo has been broken and the beam is not able to withstand the load again. Ultimate load of 12.25 KN and KN 12.985. Comparison of the mean value between the ultimate load experiment with theoretical calculations of 105.33%. Reinforcement tensile strain to work effectively while loading an average of 30.43% of ultimate loadBambu mempunyai kuat tarik yang mendekati baja normal maka dapat digunakan sebagai tulangan tarik pengganti baja. Bambu yang digunakan adalah Bambu dengan panjang 3 m, diameter pangkal 20 mm, ujung 10 mm. Balok bertulangan bambu pada penelitian ini adalah 15 cm x 20 cm x 250 cm. Penelitian ini menggunakan kekuatan karakteristik beton adalah fcâ 22 Mpa. Kuat tarik bambu walesan 147,15 MPa dan E 4900 MPa Dipasang 3 dial gauge di bawah benda uji bagian tengah. Pembebanan untuk pengujian lentur digunakan dua beban terpusat. Dari hasil penelitian dapat diketahui bahwa keruntuh lentur ditandai dengan retak-retak tegak lurus di daerah tulangan tarik. Keruntuhan balok ditandai dengan sebagian bambu telah putus dan balok tidak mampu menahan beban lagi. Beban ultimit sebesar 12,25 KN dan 12,985 KN. Perbandingan nilai rata-rata antara beban ultimit eksperimen dengan perhitungan teoritis sebesar 105,33%. Regangan tarik tulangan bekerja efektif saat pembebanan rata-rata 30,43% terhadap beban ultimit